Increased levels of CSF total but not oligomeric or phosphorylated forms of alpha-synuclein in patients diagnosed with probable Alzheimer’s disease - Nour K. Majbour (8809316) (2017)
Several studies reported an association between CSF alpha-synuclein (α-syn) and tau in Alzheimer’s disease (AD), and demonstrated the significance of α-syn in improving the diagnostic sensitivity/specificity of classical AD CSF biomarkers. In the current study, we measured CSF levels of different α-syn species in a cohort of AD patients (n = 225) who showed a CSF profile typical of AD at baseline as well as in cognitively intact controls (n = 68). CSF total α-syn (t-α-syn) significantly increased in the AD group (p < 0.0001) compared to controls, while oligomeric- and phosphorylated-Ser129-α-syn did not change significantly. ROC analysis showed a sensitivity of 85% and a specificity of 84% (AUC = 0.88) in distinguishing AD from controls. T-α-syn levels correlated positively with tau species in AD group and negatively with baseline MMSE score. Our data support the added value of measurement of CSF α-syn species for further characterization of the CSF AD profile. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/srep40263